1982
DOI: 10.1248/bpb1978.5.469
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of 13-methyl-berberrubine derivatives.

Abstract: The antitumor activity of several 13-alkyl-berberrubine and newly synthesized ester derivatives, using experimental tumors (S-180, NF sarcoma, Ehrlich carcinoma and L-1210) in mice was tested. For chemotherapeutic evaluation, the therapeutic indices and ratios were determined. Our present findings confirmed that in berberrubine derivatives, the 9-demethyl structure was essential for the manifestation of antitumor activity and demonstrated tht ester derivatives also exhibit a remarkable antitumor activity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 2 publications
1
20
0
Order By: Relevance
“…These results are well consistent with the previous reports that berberrubine is a much more potent poison of topoisomerase II than berberine . Furthermore, it has been shown that berberrubine had a strong antitumor activity in mouse models, but berberine had no antitumor activity (Ikekawa and Ikeda, 1982). Berberrubine has a hydroxyl group at the 9-position, whereas berberine contains a methoxy group at this position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are well consistent with the previous reports that berberrubine is a much more potent poison of topoisomerase II than berberine . Furthermore, it has been shown that berberrubine had a strong antitumor activity in mouse models, but berberine had no antitumor activity (Ikekawa and Ikeda, 1982). Berberrubine has a hydroxyl group at the 9-position, whereas berberine contains a methoxy group at this position.…”
Section: Discussionmentioning
confidence: 99%
“…Despite much resemblance in chemical structure, other protoberberine alkaloids such as berberine and palmatine did not act on topoisomerase II. Furthermore, it has been shown that berberrubine and its derivatives exhibit antitumor activity in mouse models, and a hydroxyl group at the 9-position of berberrubine is essential for the manifestation of antitumor activity (Ikekawa and Ikeda, 1982).…”
mentioning
confidence: 99%
“…15,16,17 In this report, we present detailed NMR studies for both berberine and berberrubine related with their biological activities by two dimensional nuclear magnetic resonance (NMR) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…16 Furthermore, it has been shown that berberrubine and its derivatives exhibit antitumor activity in mouse models, and a hydroxyl group at the 19-position of berberrubine is essential for the manifestation of antitumor activity. 17 However, the mechanism of action of these drugs that target topoisomerase II is much less clear. Their reported experimental result and suggested mechanism (an intercalation or a groove binding) is still controversial.…”
Section: Introductionmentioning
confidence: 99%